Is torosaurus triceratops? Geometric morphometric evidence of late maastrichtian ceratopsid dinosaurs. - Leonardo Maiorino (Public Library of Science (PLoS), 2013)
Background Recent assessments of morphological changes in the frill during ontogeny hypothesized that the late Maastrichtian horned dinosaur Torosaurus represents the "old adult" of Triceratops, although acceptance of this finding has been disputed on several lines of evidence. Methodology/principal findings Examining the cranial morphology of 28 skulls in lateral view and 36 squamosals of Nedoceratops hatcheri, Triceratops spp. and Torosaurus spp. by means of landmark-based geometric morphometrics, we compared ontogenetic trajectories among these taxa. Principal Component Analysis and cluster analysis confirmed different cranial morphologies. Torosaurus shape space is well separated from Triceratops, whereas Triceratops horridus and Triceratops prorsus partially overlap within Triceratops shape space. Linear regressions between shape and size suggest different ontogenetic trajectories among these taxa. Results support the "traditional" taxonomic status of Torosaurus. We hypothesize that ontogeny drives cranial morphology with different patterns between Torosaurus and Triceratops. Conclusions/significance Torosaurus is a distinct and valid taxon. Whether looking at entire skulls, skulls without the frill, frills alone, or squamosals, Torosaurus has different morphologies and distinct allometric trajectories compared to Triceratops. This new approach confirms the taxonomic status of Torosaurus as well as the comparatively low diversity of ceratopsids at the end of the Maastrichtian in North America.